2011
DOI: 10.1007/978-1-4614-0254-1_5
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Mesenchymal Stem Cells Derived from Human Bone Marrow, Umbilical Cord and Placenta: Implication in the Migration

Abstract: Umbilical cord (UC) and placenta (P) have been suggested as alternatives to bone marrow (BM) as sources of mesenchymal stem cells (MSC) for cell therapy, with both UC- and P-MSC possess immunophenotypic and functional characteristics similar to BM-MSC. However, under defined conditions, the migration capacity of BM- and P-MSC was found to be 5.9- and 3.2-folds higher than that of UC-MSC, respectively. By the use of 2-DE and combined MS and MS/MS analysis, six differentially expressed proteins were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 33 publications
7
39
0
Order By: Relevance
“…Recently, human placenta-derived MSCs were demonstrated to have higher proliferative potential than ABM-MSCs [19]. Concordant with previous reports, MSCs derived from the three different sources expressed comparable cell surface antigens as well as adipogenic and osteogenic potential [20][21][22]. In addition, they were positive for transcription factor Oct3/4, Sox-2, Nanog and c-Myc.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, human placenta-derived MSCs were demonstrated to have higher proliferative potential than ABM-MSCs [19]. Concordant with previous reports, MSCs derived from the three different sources expressed comparable cell surface antigens as well as adipogenic and osteogenic potential [20][21][22]. In addition, they were positive for transcription factor Oct3/4, Sox-2, Nanog and c-Myc.…”
Section: Discussionsupporting
confidence: 73%
“…Other molecules including ligands of selectins may also contribute to tissue-specific homing [46]. Furthermore, culture-dependent differences in expression of receptors as well as in migration of MSC [47] have been reported, and the source of cells, e.g., bone marrow, placenta and cord blood, influences migratory potential [48]. In the present study after longer culture periods, MSC showed the same chemotaxis pattern towards apoptotic neurons and cardiomyocytes.…”
Section: Discussionsupporting
confidence: 64%
“…Previously, Zhang et al, 2012, demonstrated that exosomes released from UC-MSC are internalized into umbilical cord endothelial cells and enhance in vitro the proliferation and network formation in a dose-dependent manner [37]. Interestingly, pMSC have ∼3.2-fold higher than that UC-MSC migration capacity [20]. Recently, Mineo et al ., reported that the effect of exosomes on angiogenesis involves the Src family of kinases [45].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are isolated from various sources including bone marrow (principal source), adipose tissue and placenta. Within the human placenta, MSC have been isolated from umbilical cord blood and chorionic villi [19], [20] displaying phenotypes comparable to those isolated from bone marrow, including surface antigen expression (CD45 − , CD14 − , CD19 − , CD80 + , CD86 + , CD40 + and B7H2 + ) and the capacity to differentiate into multiple linages in vitro . MSC have been implicated in wound healing and display the ability to migrate to sites of injury and engage in tissue repair and regeneration of bone, cartilage, liver tissue or myocardial cells [21], [22].…”
Section: Introductionmentioning
confidence: 99%